PENGARUH PENAMBAHAN HORMON rGH TERHADAP LAJU PERTUMBUHAN DAN EFISIENSI PAKAN IKAN BAUNG (Hemibagrus nemurus) - Putri Mutia Sari; Usman Muhammad Tang; Niken Ayu Pamukas (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACTThe research was aimed to assess the effect of giving recombinant Growth Hormone (rGH) in commercial feed with different dosage for specific growth rate, feed efficiency of (Hemibagrus nemurus). Which were treatment 0, 2, 4, 6 and 8 mg/kg of commercial feed PF 800. The experimental design used was completely randomized design with 5 treatments and 4 replicates. Catfishes at average 4-5 cm were reared in each of net cage (1x1x1) m3 in a density 20 fish/net cage for 40 days. The fish were fed with the rGH supplemented diet once a three days 10% body weight. The data observed were for specific growth rate, feed efficiency, feed convertion rate, survival rate and water quality. Data were analyzed by using ANOVA to see the difference then tested with Student Newman-Keuls to see the best treatment. The conclusion shown that the combination of rGH and commercial feed were giving affect significantly (P<0,05) for specific growth rate, feed efficiency, feed convertion rate and survival rate. Best treatment that affected the value of specific growth rate, feed efficiency, feed convertion rate and survival rate is treatment rGH with dosage of 2 mg/kg feed with value of Specific growth rate (6,52%), feed efficiency (96,50%), feed convertion rate (1,03) and survival rate (96,25%). That addition of rGH 2 mg/kg was the best treatment can improve growth and feed efficiency of (Hemibagrus nemurus) and this technology application can be useful to increase aquaculture production. Keywoard : Hemibagrus nemurus, recombinan growth hormone, growth, efisiensi pakan